Respiration in Blue-Green Algae - Biggins, John (1969)
The low rate of endogenous respiration exhibited by the blue-green algae Anacystis nidulans and Phormidium luridum was not increased by the addition of respiratory substrates. However, endogenous respiration was inhibited by low concentrations of cyanide and by high carbon monoxide tensions. In addition, the uncouplers dinitrophenol and carbonyl cyanide p-trifluoromethoxyphenylhydrazone both stimulated the respiratory rate. The transition of cells from the aerobic steady state to anaerobiosis was accompanied by a decrease in the concentration of cellular nicotinamide adenine dinucleotide phosphate (NADP(+)) and adenosine triphosphate (ATP), whereas the concentration of nicotinamide adenine dinucleotide (NAD(+)) was unchanged. Concomitant with the metabolite decreases were stoichiometric increases io reduced NADP(+) (NADPH), adenosine diphosphate, and adenosine monophosphate. A decrease in ATP was also observed after the addition of uncouplers. These data are interpreted as evidence for the association of oxidative phosphorylation with the oxidation of NADP(+)-linked substrates in these algae. Membrane fragments isolated from the algal cells oxidized succinate, malate, ferrocytochrome c, ascorbate-tetramethyl-p-phenylenediamine, and reduced 2,6-dichlorophenol indophenol but did not oxidize NADPH or reduced NAD(+) in a cyanide-sensitive system. Oxidative phosphorylation has not yet been demonstrated in these fragments, but a dark ATP-P(i) exchange, distinct from the lighttriggered exchange associated with photosynthesis, is readily observed. This exchange was inhibited by phloridzin, Atabrine, and uncouplers in concentrations which suggest that the mechanism of oxidative phosphorylation in blue-green algae is different from that found in other bacteria and in mitochondria. These results led to the conclusion that the biochemical basis for obligate autotrophy in these organisms does not lie in the metabolic events associated with terminal electron transport and energy conservation.